Volcano relationships and a new activity descriptor of 2D transition metal–Fe layered double hydroxides for efficient oxygen evolution reaction. Issue 2 (15th December 2022) - Wu, Ziyang; Liao, Ting; Wang, Sen; Li, Wei; Wijerathne, Binodhya; Hu, Wanping; O'Mullane, Anthony P.; Gu, Yuantong; Sun, Ziqi
Abstract : In two-dimensional (2D) Fe-doped MFe-LDHs, volcano-shaped relationships between the catalytic activity descriptors and the Fe contents are identified, and a new activity descriptor, the intermediate adsorption capacitance (CPEad ), is proposed. Abstract : Iron (Fe) sites play a critical role in boosting the catalytic activity of transition metal layered double hydroxide (LDH) electrocatalysts for the oxygen evolution reaction (OER), but the contribution of the Fe content to the catalysis of Fe-doped LDHs is still not well understood. Herein, a series of two-dimensional (2D) Fe-doped MFe-LDHs (M = Co, Ni, Cu, and Mn) was synthesized via a general molecular self-assembly method to track the role of Fe in their electrocatalytic OER activities. Besides the revelation of the intrinsic activity trend of NiFe > CoFe > MnFe > CuFe, volcano-shaped relationships among the catalytic activity descriptors, i.e., overpotential, Tafel slope, and turnover frequency (TOF), and the Fe-content in MFe-LDHs, were identified. Specifically, a ∼20% Fe content resulted in the highest OER performance for the LDH, while excess Fe compromised its activity. A similar volcano relationship was determined between the intermediate adsorption and Fe content via operando impedance spectroscopy (EIS) measurements, and it was shown that the intermediate adsorption capacitance (CPEad ) can be a new activity descriptor for electrocatalysts. In this work, we not only performed a systematic study on the role of Fe in 2D Fe-doped LDHs but also offer some new insights into the activity descriptors for electrocatalysts.